Developing a Task Analysis-Based E-Book for Barista Vocational Training among Individuals with Intellectual Disabilities - Tirza Dian; Asri Wijiastuti; Sujarwanto Sujarwanto (Journal of General Education and Humanities, 2026)
The participation of individuals with intellectual disabilities in the workforce remains relatively low due to limited access to adaptive vocational education and training programs. This study aimed to develop and evaluate a Task Analysis-based E-Book for barista vocational training designed to support vocational skill development among individuals with mild intellectual disabilities. The study employed a mixed-methods approach within the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development framework. Participants were seven individuals with mild intellectual disabilities aged 17–30 years enrolled at Destiny Learning Center Surabaya, selected through purposive sampling. Data were collected through expert validation sheets, practitioner practicality questionnaires, and a one-group pretest–posttest design. The results indicated that the developed E-Book achieved a high level of validity, receiving scores of 100% from the subject-matter expert, 94% from the media expert, and 92% from the special education expert. Practicality evaluation yielded a score of 84%, indicating that the E-Book was practical with minor revisions. Participants demonstrated consistent improvements in barista vocational skills, with an average N-Gain score of 0.622 (moderate category). Paired-samples t-test results showed a significant difference between pretest and posttest scores (p < 0.05). The findings suggest that the Task Analysis-based Barista Vocational E-Book is valid, practical, and has the potential to improve vocational skill performance among individuals with mild intellectual disabilities.